Increasing knock-in efficiency in mouse zygotes by transient hypothermia - Bouchareb, A; Biggs, D; Alghadban, S; Preece, C; Davies, B (Mary Ann Liebert, 2024)
Integration of a point mutation to correct or edit a gene requires the repair of the CRISPR-Cas9-induced double-strand break by homology directed repair (HDR). This repair pathway is more active in late S and G2 phases of the cell cycle, whereas the competing pathway of non-homologous end joining (NHEJ) operates throughout the cell cycle. Accordingly, modulation of the cell cycle by chemical perturbation or simply by the timing of gene editing to shift the editing towards the S/G2 phase has been shown to increase HDR rates. Using a traffic light reporter in mouse embryonic stem cells and a fluorescence conversion reporter in human induced pluripotent stem cells, we confirm that a transient cold shock leads to an increase in the rate of HDR, with a corresponding decrease in the rate of NHEJ repair. We then investigated whether a similar cold shock could lead to an increase in the rate of HDR in the mouse embryo. By analysing the efficiency of gene editing using SNP changes and loxP insertion at 3 different genetic loci, we found that a transient reduction in temperature after zygote electroporation of CRISPR-Cas9 RNP with an ssODN repair template did indeed increase knock-in efficiency, without affecting embryonic development. The efficiency of gene editing with and without the cold shock was first assessed by genotyping blastocysts. As a proof of concept, we then confirmed that the modified embryo culture conditions were compatible with live births by targeting the coat colour gene Tyrosinase and observing the repair of the albino mutation. Taken together, our data suggest that a transient cold shock could offer a simple and robust way to improve knock-in outcomes in both stem cells and zygotes.